2010
DOI: 10.3109/10253890.2010.486064
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins C and E treatment combined with exercise modulates oxidative stress markers in blood of patients with fibromyalgia: A controlled clinical pilot study

Abstract: We aimed to investigate effects of vitamins C and E (VCE) supplementation with exercise (EX) on antioxidant vitamin and lipid peroxidation (LP) levels in blood of patients with fibromyalgia (FM). A controlled study was performed on blood samples from 32 female FM patients and 30 age-matched controls. The patients were divided into three groups namely EX (n = 10), VCE (n = 11), and EX plus VCE (n = 11) after taking basal blood samples. After 12 weeks of EX and VCE supplementation, blood samples were taken once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
1
26
0
4
Order By: Relevance
“…They found no significant difference between the placebo and treatment group on any of the outcome measures. A third RCT examined vitamin C and E treatment combined with exercise versus exercise only, in FMS patients, over a period of 12 weeks [57]. Although both interventions lead to significantly higher vitamin A, C, and E serum levels, the FMS symptoms did not improve in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…They found no significant difference between the placebo and treatment group on any of the outcome measures. A third RCT examined vitamin C and E treatment combined with exercise versus exercise only, in FMS patients, over a period of 12 weeks [57]. Although both interventions lead to significantly higher vitamin A, C, and E serum levels, the FMS symptoms did not improve in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…The induction of ROS was correlated with the concentration of NPs in cells and is due to the interaction of NPs with other cellular biomolecules (Park et al, ). IONPs produce free radical species that reduce the levels of cellular antioxidants significantly, which may lead to apoptosis via oxidative damage to intracellular proteins, DNA and increased LPO (Belozerskaia and Gessler, ; Ahmad et al, ; Naziroglu et al, ; Wan et al, ). Previous studies by Konczol et al () and Kawanishi et al () have reported ROS generation in A549 and CHO cells treated with magnetite NPs.…”
Section: Discussionmentioning
confidence: 99%
“…3), which suggested that H 2 O 2 may be associated with HL-60 cells differentiation by TPA. Anti-oxidative functions of ascorbic acid have been demonstrated (35)(36)(37)(38), therefore, the present study further determined whether ascorbic acid reduces the levels of H 2 O 2 in TPA-treated HL-60 cells. The results revealed that a low-dose of ascorbic acid inhibited the increased levels of H 2 O 2 levels the TPA-treated HL-60 cells (Fig.…”
Section: Low-dose Ascorbic Acid Reduces Cellular Levels Of H 2 O 2 Inmentioning
confidence: 86%
“…A previous study demonstrated that H 2 O 2 may be a secondary messenger associated with cell differentiation (25). Several studies have demonstrated that ascorbic acid exerts anti-oxidative stress functions (35)(36)(37)(38) and a previous study demonstrated that ascorbic acid decreases levels of cellular H 2 O 2 (39). Previous studies have also reported that the ERK pathway is required for TPA-differentiated HL-60 cells (13,14).…”
Section: Ascorbic Acid Inhibits Tpa-induced Hl-60 Cell Differentiatiomentioning
confidence: 97%